2022
DOI: 10.3389/fonc.2022.975859
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics, clinical significance, and cancer immune interactions of cuproptosis and ferroptosis-associated genes in colorectal cancer

Abstract: ObjectiveTo systematically analyze the expression of cuproptosis and ferroptosis genes and their impact on the development, prognosis, tumor microenvironment (TME), and treatment response in colorectal cancer (CRC) patientsMethodsWe systematically evaluated 33 cuproptosis and ferroptosis-related genes and comprehensively identified the correlations between cuproptosis and ferroptosis-related genes and transcriptional patterns, prognosis, and clinical features. Three distinct subgroups were identified in CRC us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In a study on the prognostic risk of LGG patients, cuproptosis-related genes were analyzed by cox regression together with necroptosis-related genes, and the five genes that contributed most to the model construction were selected to construct the prognostic signature, however, these 5 genes were all considered to be necroptosis related in previous studies [ 189 ]. In the study on CRC, investigators selected cuproptosis-related genes together with ferroptosis-related genes to construct a prognostic signature, however, the contribution of each gene to the model was not described [ 190 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on the prognostic risk of LGG patients, cuproptosis-related genes were analyzed by cox regression together with necroptosis-related genes, and the five genes that contributed most to the model construction were selected to construct the prognostic signature, however, these 5 genes were all considered to be necroptosis related in previous studies [ 189 ]. In the study on CRC, investigators selected cuproptosis-related genes together with ferroptosis-related genes to construct a prognostic signature, however, the contribution of each gene to the model was not described [ 190 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that ferroptosis and cuproptosis might involve the pathology of NAFLD. Interestingly, ferroptosis and cuproptosis are both associated with CRN (especially CRC) ( Li et al, 2022 ; Zhang et al, 2022 ). This finding urged us to pursue the potential significance of ferroptosis and cuproptosis in NAFLD-related CRN (here we use CRC as an example), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Iron-sulfur cluster proteins play a key role in cuproptosis and their homeostasis is involved in cuproptosis-dependent cancer therapy. Several recent studies have shown that cuproptosis-associated genes, including iron-sulfur clusters, are potential predictors of diagnostic, prognostic, and therapeutic response in some cancers and are associated with tumor microenvironment, immune response and immunotherapy [143][144][145][146][147].…”
Section: Iron-sulfur Clusters and Cuproptosismentioning
confidence: 99%